Using rubrics to explore pathways to scale: Navigating the Integration of Graduation into Public Systems - Blog post on Better Evaluation - Pellini, Arnaldo; Torres, Kristian Paolo; Warokka, Tania Dora (Better Evaluation, 2026)
In this blog, Arnaldo Pellini, Kristian Paolo Torres, and Tania Dora Warokka reflect on their experience developing and testing a rubric to support dialogue and learning as complex initiatives are integrated into public systems.

Outcomes & Systems: From Predicted Goods to Emergent Cohesion - Johar, Indy (Indy Johar, 2025)
Critical summary – the single through‑line of the essay

Review of current system & portfolio practices in the development sector: Organizational… - Pereverza, Kateryna (Medium, 2024)
Building on interviews with colleagues in development organizations, donor & partner governments and foundations, this article explores the adoption of system and portfolio-based approaches in the development sector focusing on organizational motivations and challenges, changes in the network of the development sector actors, and types of collaborative experiments initiated around the novel approach. The aim is to take steps towards understanding how this type of approach for system change can be institutionalized in the sector and become one of the main ways of operating for delivering transformative impact. Summary While there is a broad consensus that linear, fragmented, projectized ways of doing development & public policy are not a match for the type of context we live in today, there is less consensus about what alternatives look like. In this space, system and portfolio approaches have emerged during the last few years and a new field is beginning to slowly emerge. Currently, there is a diversity in interpretations of system and portfolio-based approaches by the development sector organizations. This is connected to different logics and theories of transformative change in complex systems. Also, the intent with the adoption of the novel approach can vary along the dimension of organizational efficiency vs place-based transformations. Organizations engage with portfolio-based approaches with different intents and in different roles. For example, OECD OPSI takes forward the innovation portfolio management for partners; the European Commission funds place-based portfolios e.g. within the M4EG program; while UNDP facilitates place-based and thematic portfolios for system transformations. When it comes to the motivations of development sector partners to experiment with system and portfolio-based approaches, these include increased effectiveness & efficiency of the use of funds for place-based transformations; response to the post-colonial critique; creation of visibility as a frontrunner; the potential of joint risk-taking; the opportunity of collective learning from an entire portfolio (coherence & dynamic evolution); and directionality added to internal and external activities. Challenges encountered by partners engaged in the experimentation with system and portfolio-based approaches are connected to resources and time constraints that emerge from the prevailing logics & constraints of current organizational structures premised on fragmentation & projectization; organizational leadership dynamics; the influence of dominant organizational culture and mindsets; the difficulties of adopting the ‘portfolio language’/jargon; prevailing funding structures and cycles; and a shortage of both time and capacity to engage with numerous local partners. The structure of the development sector ecosystem is undergoing changes driven by a rapidly changing context. The experimentation with system and portfolio-based approaches has led to new actors joining the space, such as innovative consultancies developing the logic of transformative change in systems and facilitating portfolios on the ground, and the emergence of new roles and relationships, for example, ‘learning partners’. Since 2020, three noticeable types of collaborative experiments emerged in the development sector ecosystem: systemic investments; thematic and place-based portfolio interventions; and monitoring, evaluation and learning (MEL) for the context of system change. This study revealed areas for further exploration and analysis. One is a need to co-create institutional structures to enable a co-ownership of place-based portfolios by several international partners as well as local stakeholders. Another area connects to the need to create and implement spaces and tools for collective learning from portfolios. Finally, there is a need to understand what mechanisms can enable the institutionalization of novel approaches on the level of the entire sector and their interconnection with organizational changes needed. This study is based on the interviews with representatives of ten development sector organizations conducted in spring 2023 and insights shared within portfolio practitioner gatherings and the M&E Sandbox webinars run during 2023. Introduction: The article emphasizes the importance of (re)framing challenges in portfolio-based approaches for steering system transformations. It acknowledges that the way we frame challenges significantly influences the solutions we develop, and therefore, it’s crucial to address the right problems rather than wasting resources on incorrect issues. Study Insights: The insights come from a study initiated in autumn 2021, focusing on how framing processes unfold, what needs to be framed, the open-ended nature of framing, and the roles international organizations like UNDP can play in developing inclusive and system transformation-oriented framings of urban challenges. Key Points: The study involved interviews with experts from the UNDP Istanbul and Thailand Regional hubs. It explored the experimentation with the portfolio approach in collaboration with local and national governments and partners. The article presents insights related to the framing process and highlights open questions for researchers and practitioners. System Transformations: System transformations require a deep understanding beyond surface-level issues, as existing systems often limit our imagination and prevent us from exploring the root causes of complex societal challenges. Portfolio Approaches: The article references the collaboration between the Swedish Strategic Innovation Programme “Viable Cities” and the Strategic Innovation Unit of UNDP. They focus on portfolio-based approaches for urban low-carbon transitions in Sweden, targeting the mission: “Climate-neutral cities 2030 with a good life for all within planetary boundaries.” Conclusion: The blog post concludes by highlighting the need for further research and practice in developing effective portfolio approaches to address complex societal challenges.

Practicing what we preach — our experience rethinking M&E in complex settings - Bina, Andrea; Vester, Søren (UNDP Strategic Innovation, 2023)
The UNDP has been exploring new approaches to M&E to better understand and address complex systems challenges. Traditional linear project-based planning and evaluation methods are insufficient for dealing with the unpredictable nature of such systems. The UNDP’s new Strategic Plan calls for a shift in M&E practices to align with the complexity of today’s global challenges. Key points from the blog post include: Learning and Adapting: There’s a need for continuous learning and adaptation in M&E practices to effectively address complex problems like transitioning to a circular economy. Longer Time Horizons: Substantive change takes time, and it’s often unclear what the results will look like, making it difficult to track progress. Aggregate Impact: Evaluating interconnected interventions as a portfolio is crucial because they cannot be assessed in isolation. Contribution vs. Attribution: Focusing on the contribution to broader change processes is more important than attributing specific outcomes to individual actions. The UNDP has initiated the M&E Sandbox to experiment with and learn from innovative M&E practices. This collaborative space has attracted participants from over 180 organizations, highlighting a shared interest in evolving M&E to better understand change in contexts of uncertainty. A partnership with the Bill and Melinda Gates Foundation has also been formed to focus on M&E in food systems. The blog post emphasizes the importance of embracing uncertainty, experimenting, and collaborating to contribute to positive change in complex settings1.

From mouthset to mindset shifts in co-creating systems change - Blomkamp, Emma; Snow, Thea; Burkett, Ingrid (Griffith Centre for Systems Innovation, 2023)

Innovative M&E from the Sandbox and beyond - Vester, Søren; Tran, Samuel (Medium, 2023)
In this blog we are sharing a digest of some of the many useful and innovative monitoring, evaluation and learning resources and efforts that have come through the M&E Sandbox in 2022. A lot of these resources have been shared by our community in response to the overwhelmingly positive feedback from the launch of the Sandbox (please keep them coming!). We hope you find it useful. We have grouped these efforts and resources under six broad questions: - How do we measure systems transformation? - How do we know if we are on track? - How do we rethink complexity and independence in evaluation? - Why, how and for whom do we measure? - How do we generate insights and learn? - How do we make decisions and adapt?

What, so what, now what? - Aston, Thomas (Medium, 2022)
Getting serious about systems change

Towards ‘Targeted Systems Change’ - Rye, Sam (Fieldnotes by Sam Rye, 2019)
Modelling and communicating how to shift systems